Lactobacillus rhamnosus strains of oral and vaginal origin show strong antifungal activity in vitro. Issue 1 (1st January 2020) - Rose Jørgensen, Mette; Thestrup Rikvold, Pernille; Lichtenberg, Mads; Østrup Jensen, Peter; Kragelund, Camilla; Twetman, Svante
ABSTRACT: Background: Intake of probiotic bacteria may prevent oral  Candida  infection. Objective: To screen the antifungal activity of 14  Lactobacillus  candidate strains of human origin, against six opportunistic  C. albicans  and non-albicans species. A second aim was to study the acid production of the four strains showing the strongest antifungal activity. Methods: We used an agar overlay growth inhibition assay to the assess the antifungal activity of the lactobacilli. The acid-producing capacity was measured with pH micro-sensors. Results: All 14  Lactobacillus  candidates inhibited the growth of the  Candida  spp. The four best-performing strains were  L. rhamnosus  DSM 32992 (oral origin),   L. rhamnosus  DSM 32991 (oral),   L. jensenii  22B42 (vaginal), and  L. rhamnosus  PB01 (vaginal). The difference between  L. rhamnosus  DSM 32992 and the other three strains was statistically significant (p < 0.001). The  Candida  spp. differed in susceptibility;  C. parapsilosis  was highly inhibited, while  C. krusei  was not or slightly inhibited. The oral  L. rhamnosus  DSM 32992 and DSM 32991 strains showed the lowest pH-values. Conclusion: Screening of probiotic lactobacilli showed significant strain-dependent variations in their antifungal capacity in a pH-dependent mode. Two strains of oral origin were most effective. A further characterization seems justified to elaborate on their probiotic properties.